Between the Microworld and the Macroworld - Grygiel, Wojciech (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
The current 50th issue of Philosophical Problems in Science (Zagadnienia Filozoﬁczne w Nauce) summarizes the eﬀorts of both philosophers and scientists to understand how a broader philosophical context sets the stage for the development of scientiﬁc research, with physics playing a leading role. In particular, the paper reviews the content of the last twenty-ﬁve issues of the journal with an emphasis on the philosophical problems that arise in the practice of physics. The overview reveals that these problems reﬂect the main conceptual division in physics between the treatment of the micro-world described by quantum mechanics and the macro-world governed by the general theory of relativity. Both of these theories, taken separately, generate a host of philosophical concerns such as their proper interpretation (Bell’s Theorem and its consequences) or the meaning and the eventual validity of the notions of space and time. Other philosophical problems in physics, such as chaos and determinism, are also considered. The authors are well aware that the formulation of the future theory of quantum gravity will be a demanding task requiring profound philosophical reﬂection.